Black Carbon in Reykjavík: Traffic Related Pollution in a Cold Climate City - Bergljót Hjartardóttir 1986- (2021)
Concern is growing over black carbon (BC, or soot) which is emitted to the atmosphere via fossil fuel burning. BC is the most harmful component of Particulate Matter (PM) pollution and the third biggest contributor to global warming. This study´s goal was to assess the potential exposure to traffic related BC in Reykjavík via three modes: Walking along the highway, driving on the highway and walking in a residential area near the highway. To attain these goals, 20 measurement campaigns were conducted near or along Miklabraut Highway during three seasons known for poor traffic related air quality: Christmas, winter and spring (2017-2018) during morning and afternoon traffic hours. The maximum, median and minimum mobile BC levels of exposure for all campaigns were 11.4, 2.5, 0.9 µg/m3, 8.6, 2.3, 0.3 µg/m3 and 4.5, 0.8, 0.1 µg/m3 for drivers on the highway, pedestrians along the highway and habitants in a neighborhood adjacent to the highway, respectively. Exposure trends showed high seasonal variability, with the highest BC in Christmas and the lowest in spring. Spatial distribution revealed hotspot formations on intersections and typical traffic congestion sites and pollution spreading into the adjacent residential neighborhood. BC correlated with temperature, wind speed, relative humidity and near ground temperature inversions. High correlation between NO2 and BC was observed, indicating that stationary NO2 measurements at the Grensásvegur air quality station was a good indicator for overall BC exposure during commuting by Miklabraut Highway. Median BC exposure by Miklabraut is similar to busy roads in three European capitals. Vaxandi ógn við loftslag og loftgæði er sót (e. Black carbon, eða BC) sem verður til við bruna jarðefnaeldsneytis. Sót er hættulegasti hluti svifryks og þriðji stærsti valdur hlýnunar jarðar. Markmið þessarar rannsóknar var að meta mögulega útsetningu almennings fyrir umferðartengdri sótmengun í Reykjavík gegnum þrjár útsetningarleiðir: ganga meðfram umferðarþungri götu, keyra á ...